2015
DOI: 10.1002/chem.201406648
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Keplerate Type‐Cluster “Mo132” Cavity with Dicarboxylate Anions

Abstract: The internal functionalization of the Keplerate-type capsule Mo132 has been carried out by ligand exchange leading to the formation of glutarate and succinate containing species isolated as ammonium or dimethylammonium salts. Solution NMR analysis is consistent with asymmetric inner dicarboxylate ions containing one carboxylato group grafted onto the inner side of the spheroidal inorganic shell while the second hangs toward the center of the cavity. Such a disposition has been confirmed by the single-crystal X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…The final refinement was done accordingly with 24 coordinated valerate ligands (C atoms of the carboxylate group have an 80 % occupancy). A similar composition has been quite recently reported for a glutamate‐type capsule …”
Section: Figuresupporting
confidence: 85%
“…The final refinement was done accordingly with 24 coordinated valerate ligands (C atoms of the carboxylate group have an 80 % occupancy). A similar composition has been quite recently reported for a glutamate‐type capsule …”
Section: Figuresupporting
confidence: 85%
“…The Linqvist structure [M 6 O 19 ] xand its derivatives (Figure 1) are probably the main archetypical structure of this class but in the domain of isopolyoxomolybdates, Müller et al opened a new field of investigation when they reported the discovery of a fullerene-like, all-inorganic hollow spheres containing 132 molybdenum centers in 1998 (Figure 1). [30] [21,[31][32][33] Not only aesthetic, these nanometric hollow clusters behave as functional nanoflasks for cations or molecules trapping, [34][35][36][37] catalysis [38] or specific chemical transformations. [39] This family of polyoxomolybdates was also complemented by other giant POMs namely the "big wheels" {Mo-154}, {Mo-176} and {Mo-248}, and the "blue lemon" {Mo-368}, which expanded the frontiers of inorganic chemistry to the mesoscopic world (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…These ligands are usually bidentate oxygen donor anions, such as formate, [5] acetate, [2b] monochloroacetate, [5c] sulfate, [2b, 6] sulfite, [7] hypophosphite, [8] hydrogen phosphate, [9] selenate, [10] valerate, [11] carbonate, [8] carboxylates in general, [12] or even dicarboxylates. [13] Thesel igands are labilely bonded to the inner surface of the capsule. Therefore, they are able to exchange their positions insideo ft he Keplerate or even with solvated anionsf rom the outer medium through the pores.…”
Section: Introductionmentioning
confidence: 99%
“…In the general formula of Keplerates, L represents a bidentate ligand that can be coordinated to the inner surface of the capsule. These ligands are usually bidentate oxygen donor anions, such as formate, acetate, monochloroacetate, sulfate, sulfite, hypophosphite, hydrogen phosphate, selenate, valerate, carbonate, carboxylates in general, or even dicarboxylates . These ligands are labilely bonded to the inner surface of the capsule.…”
Section: Introductionmentioning
confidence: 99%